Danish Modernist Architecture and Furniture Design in Passenger Ship Interiors 1935–1965. Issue 3 (3rd July 2019) - Peter, Bruce
Abstract : Since the 1960s Denmark has become internationally renowned for its architecture and design output. The work of Danish modernist architects and designers working on terra firma is very well known, but very little has been written about their influence on the design of merchant ships. This article examines the manifestation of Danish architectural modernism in the interior design of Danish and other Scandinavian-owned passenger ships built between the mid-1930s and the mid-1960s. It explains how the Danish Modern Movement in architecture and design had distinct characteristics from other avant-gardes in visual culture of the early-to-mid twentieth century and argues that its respect for tradition was advantageous when engaging with ship owners, naval architects and shipbuilders. It focuses in particular on ship interiors designed by the architects Kay Fisker, Palle Suenson and Kay Kørbing and shows how their designs became 'floating ambassadors' for Danish and Scandinavian modernism more generally.